PENGETAHUAN DAN PEMANFAATAN TUMBUHAN OBAT TRADISIONAL MASYARAKAT SUKU MORONENE DI DESA RAU-RAU SULAWESI TENGGARA (Study and Utilization Of Traditional Medicine Plants By Morenene Ethnic In Rau-Rau Village, Southeast Sulawesi) - ., Indrawati; Sabilu, Yusuf; Ompo, Alda (Jurnal BioWallacea, 2014)
Research on the Study and utilization of Traditional medicine plants by Moronene ethnic in the Rau-Rau village Southeast Sulawesi were aims to: 1) inventory these kinds of medicinal plants are utilized including the identification of scientific and local names, 2) study the knowledge society in the utilization of plants as medicine, metods processing and the efficacy, 3) study the  knowledge kinds of disease and how to use of medicinal plants. With methods survey exploration conducted interviews to expert treatment (sandro) and the community. There are 51  spesies plant  in 27 family growing in the backyard, in the gardens and in the forests around the settlement. The organ  medicinal plant species (leaves, stems, bark, rhizome, tuber, fruit and SAP) are uses for tradisional medicines to cure about 36 kids of diseases. Method of use will discussed in this paper.   Keywords: Medicine Plants, Rau-rau Village Sociaty Moronene